2017
DOI: 10.4103/0976-9668.198344
|View full text |Cite
|
Sign up to set email alerts
|

Xylitol in preventing dental caries: A systematic review and meta-analyses

Abstract: Xylitol is a sugar alcohol having the properties that reduce levels of mutans streptococci (MS) in the plaque and saliva. To assess the role of xylitol in preventing dental caries. Systematic review and meta-analysis developed by Cochrane cooperation were adapted. Electronic search was carried out in PubMed through the period up to 2014. Included clinical studies were done on (1) humans (2) participants include both individuals and as pairs (mother-child) (3) participants using orthodontic appliances (4) xylit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
1
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 20 publications
1
59
1
7
Order By: Relevance
“…Several studies have demonstrated that xylitol possesses important oral health applications, especially for the control of cariogenic bacteria . Earlier studies evaluated the inhibitory effect of xylitol on the formation of Streptococcus mutans , Streptococcus mitis , and Streptococcus sanguinis biofilms, demonstrating that xylitol has the ability to inhibit the formation of biofilm mass by about 68% when used as a sucrose substitute.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that xylitol possesses important oral health applications, especially for the control of cariogenic bacteria . Earlier studies evaluated the inhibitory effect of xylitol on the formation of Streptococcus mutans , Streptococcus mitis , and Streptococcus sanguinis biofilms, demonstrating that xylitol has the ability to inhibit the formation of biofilm mass by about 68% when used as a sucrose substitute.…”
Section: Resultsmentioning
confidence: 99%
“…Substances able to interfere with bacterial adhesion on oral surfaces are of great importance for biofilm control and oral health maintenance. Xylitol, which is used as a sucrose substitute, has many clinical applications owing to its anticariogenic and antiadherent effects that are mediated by a reduction of the adhesion of bacteria important for biofilm formation . Studies demonstrate that xylitol inhibits oral biofilm formation but the exact mode of action for biofilm inhibition is still not completely understood.…”
mentioning
confidence: 99%
“…In a recent systematic review, Janaldram et al 48 defended the use of xylitol over other preventive strategies. They considered that the use of xylitol in products suitable for self-application could be considered an effective strategy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that it is due to influence of multiple factors including use of fluoride, enhanced oral hygiene including brushing and flossing, dietary changes, xylitol and specific procedure performed in dentists office such as routine examination including diagnostic radiographs, scaling and polishing, fluoride applications, and sealant [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%